(untitled) (Med Phoenix, 2023)
Introduction: Premature Menopause is defined as premature ovarian failure before the age of 40 years with a consecutive 12 months of amenorrhea. Menopause affects 1% of women under the age of 40 years. It is seen in 10‑28% of primary amenorrhea and 4‑18% of secondary amenorrhea. Estrogen deficiency occurring during premature menopause causes decrease in HDL level and increase in LDL, cholesterol and triglycerides levels thus causing dyslipidemia. Regardless of cause, women who experience estrogen deficiency at an early age before the natural menopause are now considered to be at increased risk for premature morbidity and mortality. The current study is aimed to find out the impact of premature menopause on the blood lipid level in the current population. Materials and Methods: Ninety-six cases of premature menopause women were enrolled retrospectively for the study. Complete Lipid profile – Serum Total Cholesterol, Serum Triglyceride, Serum HDL, were measured in fully automated biochemistry analyzer and Serum VLDL and Serum LDL were estimated by Friedewald’s Formula. Results: The current study revealed the lipid profile status of premenopausal women. The prevalence of dyslipidemia was observed in 57 cases (59.4%) and remaining 39 cases (40.6%) were having normal lipid levels. On comparing the serum lipid levels statistical significance were observed in Total cholesterol (P value: 0.00), Triglyceride (P value: 0.00), LDL-C (P value: 0.00), and VLDL-C (P value: 0.00). However, no statistically significant difference was observed in HDL cholesterol (P value: 0.15). Conclusions: Serum Lipid levels is deranged in the women with premature menopause (Age < 40 years) and thus dyslipidemia, particularly noticed with the Total cholesterol and triglyceride levels. The path-physiology lying behind dyslipidemia can be correlated to the premature ovarian failure and estrogen deficiency.